Under prairie skies : the plants and native peoples of the Northern Plains - Shay, C. Thomas (Creighton Thomas) (University of Nebraska Press, 2022)
"In Under Prairie Skies, C. Thomas Shay asks and answers the question: What role did plants play in the lives of early inhabitants of the northern Great Plains? Since humans arrived at the end of the Ice Age, plants played important roles as Native peoples learned which were valuable foods, which held medicinal value, and which were best for crafts. Incorporating Native voices, ethnobotanical studies, personal stories, and research techniques, Under Prairie Skies shows how, since the end of the Ice Age, plants have held a central place in the lives of Native peoples. Eventually some groups cultivated seed-bearing annuals and, later, fields of maize and other crops. Throughout history, their lives became linked with the land, both materially and spiritually. "--